A Comparative Analysis of Qibla Direction Accuracy Using a Theodolite, Mizwala, and Right-Angle Triangle at As-Sakinah Mosque, Surabaya - Safna Farah Dila (Astroislamica: Journal of Islamic Astronomy, 2025)
The Qibla direction is a fundamental aspect of Muslim prayer, requiring precise determination. This study evaluates the accuracy of the Qibla direction at the As-Sakinah Mosque in Surabaya by comparing three instruments: a Theodolite, a Mizwala, and a Right Triangle (Segitiga Siku-siku). Employing field experimental methods, the measurement data were analyzed using a comparative descriptive approach. The findings reveal significant variations in accuracy among the instruments: the Theodolite and Mizwala detected deviations of 5° 56' 48.71" and 5° 35' 4.21" respectively, whereas the Right Triangle method showed a substantial deviation of 25°. It is concluded that the mosque's current orientation deviates by approximately 5 degrees to the North, highlighting that digital optical instruments offer superior accuracy compared to simple manual methods in urban environments.